X-ray evaluation of high-verticality sidewalls fabricated by deep reactive ion etching. (10th May 2017) - Takeuchi, Kazuma; Ezoe, Yuichiro; Ishikawa, Kumi; Nakamura, Kasumi; Numazawa, Masaki; Terada, Masaru; Fujitani, Maiko; Ishi, Daiki; Noda, Yusuke; Ohashi, Takaya; Morishita, Kohei; Nakajima, Kazuo; et al.
Abstract: We report the fabrication and characterization of high-verticality sidewalls by deep reactive ion etching (DRIE). We quantitatively evaluated the verticality of the sidewalls with a width of 20 µm and a depth of 300 µm by using an X-ray beam (1.49 keV). To the best of our knowledge, we succeeded in constraining the verticality and smoothness of the DRIE-fabricated sidewalls with the highest accuracy. The verticality of the sidewalls against the wafer surface was estimated from the shifts of the X-ray focus to be 8.7 ± 3.2 arcmin on average within the wafer, while the resolution of the X-ray focus was 21.1 ± 2.7 arcmin in half-power diameter. Although the verticality and resolution require further improvements, we verified that the X-ray imaging technique is valid for quantifying the sidewall properties.